Recurrent Membranoproliferative Glomerulonephritis Type I After Kidney Transplantation: A 17-Year Single-Center Experience. Issue 6 (June 2015) - Green, Hefziba; Rahamimov, Ruth; Rozen-Zvi, Benaya; Pertzov, Barak; Tobar, Ana; Lichtenberg, Shelly; Gafter, Uzi; Mor, Eytan
Abstract : Background: Most previously published studies of patients with membranoproliferative glomerulonephritis type I are small or have short follow-up period. We report the outcome of a fairly large cohort of patients followed up for nearly 10 years. Methods: Retrospective cohort study. Graft survival, recurrence rate and risk factors for recurrence were analyzed for 43 patients transplanted between the years 1995 and 2012. Results: At a mean overall follow-up of 118±61 months (median, 127.8; range, 4.9–217), 12 patients lost their graft (28%). Death-censored actuarial 15-year graft survival rate was 56%. Membranoproliferative glomerulonephritis recurred in eight patients (19%) at a median time of 15.4 months (range, 4.4–70 months). Recurrence led to graft loss in seven patients (88%) within a median of 11.6 months (range, 1.3–54 months) from diagnosis. Median graft survival was 30.5 months for recurrence (range, 7–86). Actuarial 15-year graft survival was 71% for nonrecurrent. The risk for recurrence was higher for patients with human leukocyte antigen (HLA) B49 (odds ratio, 16.9; 95% confidence interval, 1.1–246; P =0.038) and HLA DR4 (odds ratio, 15.9; 95% confidence interval, 1.07–237; P =0.044) alleles. A trend toward increased risk was found with shorter duration of dialysis before transplantation. Four of 16 (25%) living-related versus none of the living-unrelated donors' recipients recurred. The HLA B49, acute tubular necrosis after transplantation, previous transplantations, and Arab origin were all associated with decreased graft and patient survival. Conclusion: Patients without recurrence in the first years should expect an excellent graft survival. Nonrelated living donors should be preferred. The HLA B49 and DR4 alleles may increase the risk for recurrence. Abstract : An analysis of a large cohort of kidney transplant recipients with membranproliferative glomerulonephritis type 1 shows that non-recurrence within the first year after transplant and living nonrelated transplantation result in excellent long-term outcomes.